Nanostructured copper selenide as an ultrasensitive and selective non-enzymatic glucose sensor. Issue 3 (8th December 2020) - Umapathi, Siddesh; Singh, Harish; Masud, Jahangir; Nath, Manashi
Abstract : CuSe nanostructures exhibit high-efficiency for glucose detection with high sensitivity (19.419 mA mM −1 cm −2 ) and selectivity at low applied potential (0.15 V vs. Ag|AgCl), low detection limit (0.196 μM) and linear detection range (100 nM to 40 μM). Abstract : CuSe nanostructures exhibit high-efficiency for glucose detection with high sensitivity (19.419 mA mM −1 cm −2 ) and selectivity at a low applied potential of +0.15 V vs. Ag|AgCl, a low detection limit of 0.196 μM and a linear range of glucose detection from 100 nM to 40 μM.